DNA methylation modifications induced by hexavalent chromium. (3rd July 2019) - Guo, Xinnian; Feng, Lingfang; Lemos, Bernardo; Lou, Jianlin
Abstract: Hexavalent chromium [Cr (VI)] contributes a significant health risk and causes a number of chronic diseases and cancers. While the genotoxic and carcinogenic effects of hexavalent chromium exposure are explicit and better-characterized, the exact mechanism underlying the carcinogenic process of Cr (VI) is still a matter of debate. In recent years, studies have shown that epigenetic modifications, especially DNA methylation, may play a significant role in Cr (VI)-induced carcinogenesis. The aim of this review is to summarize our understanding regarding the effects of Cr (VI) on global and gene-specific DNA methylation.